Engaging with difference: Integrating the linguistic landscape in virtual exchange. (April 2022) - Vinagre, Margarita
Abstract: In this article we present the findings from a virtual exchange project between undergraduate students of English at a Spanish university and students of Spanish at an American university. After engaging in information exchange, comparison and discussion of four cultural topics using WordPress and Zoom, the final task involved exploring the linguistic landscape and how the foreign/second language was used in their respective cities in order to encourage cultural awareness and engagement with difference. Data analysis included quantitative analysis (descriptive statistics) and qualitative analysis (coding and categorization) of the photos taken by the students in addition to qualitative analysis (open and axial coding, Grounded theory) of the content of their reflection essays. Results suggest that the students engaged with difference at deep levels and that, when integrated in virtual exchange, issues relating to social representation and identity can be negotiated and differences can be acknowledged and valued.